Camino winds [compact disc, unabridged] - Grisham, John (Grisham, John. Camino series., 2020)
After riding out a hurricane in his home on Camino Island, novelist Bruce Cable investigates the connection between real life and fiction when his friend, thriller writer Nelson Kerr, is found dead, apparently from the storm, but with several suspicious blows to the head.